Polarized Secretion of APRIL by the Tonsil Epithelium Upon Toll-Like Receptor Stimulation - Sturm, Nathalie; Quinterot, Melanie; Guyot, Jean-Philippe; Righini, Christian; Daamen, Willeke F.; van Kuppevelt, Toin H.; Huard, Bertrand (Frontiers in Immunology, 2021)
Abstract In mucosa such as tonsil, antibody-producing plasmocytes (PCs) lie in sub-epithelium space, which is thought to provide a suitable environment for their survival. A proliferation inducing ligand (APRIL) is one key survival factor for PCs present in this area. According to in situ staining, apical epithelial cells produced APRIL, and the secreted product had to migrate all through the stratified surface epithelium to reach basal cells. A similar process also occurred in the less organized crypt epithelium. Tonsil epithelial cells captured secreted APRIL thanks to their surface expression of the APRIL co-receptor, either syndecan-1 or -4 depending on their differentiation stage. In the most basal epithelial cells, secreted APRIL accumulated inside secretory lamp-1+ vesicles in a polarized manner, facing the sub-epithelium. The tonsil epithelium up-regulated APRIL production by apical cells and secretion by basal cells upon Toll-like receptor stimulation. Furthermore, LPS-stimulated epithelial cells sustained in vitro PC survival in a secreted APRIL-dependent manner. Taken together, our study shows that the tonsil epithelium responds to pathogen sensing by a polarized secretion of APRIL in the sub-epithelial space, wherein PCs reside.